Variations in the Innervation of the Long Head of the Triceps Brachii: A Cadaveric Investigation. Issue 1 (January 2017) - Erhardt, Alexandra J.; Futterman, Bennett
Abstract: Background: Some leading anatomy texts state that all three heads of the triceps brachii are innervated by the radial nerve. The posterior cord of the brachial plexus bifurcates to terminate as the radial and axillary nerves. Studies have noted the presence of axillary innervation to the long head of the triceps brachii muscle, patterns different from the classic exclusive radial nerve supply. An understanding of these variations may assist the clinician in the assessment of shoulder weakness and in preoperative and operative planning of radial and axillary neuropathies. Questions/Purpose: We aimed to further investigate, in cadaver dissections, the prevalence of axillary nerve contribution to the innervation of the long head of the triceps brachii. Methods: We performed bilateral brachial plexus dissections on 10 embalmed cadavers combining anterior axillary and posterior subscapular approaches. Two additional unilateral cadaveric brachial plexuses were dissected. The posterior cords were fully dissected from the roots distally. The radial and axillary nerves were followed to their muscle insertion points, the dissections were photographed, and the length of branching segments were measured. Results: Of the 10 paired cadavers dissected (20 specimens), in only one of the 10 cadavers was the classic innervation pattern of radial nerve observed. The other nine cadavers had varying patterns of radial and axillary nerve innervation, The observed patterns were radial and axillary (dual) on one side with radial alone on the other, dual innervation bilaterally, or axillary with contralateral radial innervation. The two additional unilateral dissected specimens were innervated exclusively by the axillary nerve. Conclusions: Gross and surgical anatomy sources state that the radial nerve is the sole nerve supply to the long head of the triceps. In our study sample, pure radial innervation of the long head of the triceps brachii was not the predominant nerve pattern. We found four other studies that looked at axillary innervation of the long head of the triceps; of the 62 total cadaver shoulders examined in those studies, 71% were found to have nonclassic innervation patterns. Nonclassic patterns may include purely axillary, dual, or posterior cord innervation to the long head of the triceps, and may account for the majority of innervation to the long head of the triceps. These are similar to our findings. Clinical relevance: Understanding the innervation of the long head of the triceps and variations in axillary nerve course is critical to the clinical diagnosis of injury, surgical treatment options, and rehabilitation of axillary nerve injuries. With this information, the practitioner may have additional surgical options, clearer rationales for clinical situations, and explanations for patient outcomes.